2016
DOI: 10.3389/fphar.2016.00323
|View full text |Cite
|
Sign up to set email alerts
|

High-density Lipoproteins and Apolipoprotein A-I: Potential New Players in the Prevention and Treatment of Lung Disease

Abstract: Apolipoprotein A-I (apoA-I) and high-density lipoproteins (HDL) mediate reverse cholesterol transport out of cells. Furthermore, HDL has additional protective functions, which include anti-oxidative, anti-inflammatory, anti-apoptotic, and vasoprotective effects. In contrast, HDL can become dysfunctional with a reduction in both cholesterol efflux and anti-inflammatory properties in the setting of disease or the acute phase response. These paradigms are increasingly being recognized to be active in the pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 61 publications
3
77
1
1
Order By: Relevance
“…One of the main effects of this resveratrol‐derived drug is the increase in APOA1 transcription. An anti‐tumorigenic activity of this lipoprotein has already been described against melanoma (Zamanian‐Daryoush et al ., a) as well showing a protective role against the development of a variety of lung diseases, including lung cancer (Gordon et al ., ). Moreover, several studies have shown that APOA1 levels can be considered a biomarker with reduced plasma levels in patients with early stage ovarian cancer compared with normal individuals (Clarke et al ., ; Kim et al ., ; Kozak et al ., ; Moore et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…One of the main effects of this resveratrol‐derived drug is the increase in APOA1 transcription. An anti‐tumorigenic activity of this lipoprotein has already been described against melanoma (Zamanian‐Daryoush et al ., a) as well showing a protective role against the development of a variety of lung diseases, including lung cancer (Gordon et al ., ). Moreover, several studies have shown that APOA1 levels can be considered a biomarker with reduced plasma levels in patients with early stage ovarian cancer compared with normal individuals (Clarke et al ., ; Kim et al ., ; Kozak et al ., ; Moore et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…19 Subsequently, the IFN-γ produced by recruited stimulated lymphocytes, which has been described to be crucial for Th1 immunity and trastuzumab response, 26 would in turn induce CXCLs in tumor cells followed by improved T cell-trafficking and maintenance of immune-enriched TME. Although tumor antigenicity derived from a high mutational burden, as demonstrated in patients with melanoma and lung cancer who respond to immune-checkpoint inhibitors, 27-29 may also explain the infiltration of HER2+ BCs by adaptive immune cells, the low mutational burden of BCs compared to melanoma 30 and the lack of association between the amount of neoantigens and TIL count or trastuzumab activity in tumors from patients enrolled in the FinHer trial 31 do not support this possibility. Considering that CXCLs and HER2 mRNA levels are significantly positively correlated in HER2+ BC samples and in our in vitro models, it could be hypothesized that these molecules are co-regulated in trastuzumab responsive HER2-addicted tumors, the subgroup with the highest HER2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown that an abnormal level of lipid profile may influence carcinogenesis and is closely linked to tumor progression [12]. Cholesterol synthesis is raised in cancer cells compared with normal cells, as tumor cells require excess cholesterol and intermediates of the cholesterol biosynthesis pathway to sustain a high level of proliferation [13].…”
Section: Introductionmentioning
confidence: 99%